Determinants of Mode Share over Time: How Changing Transport System Affects Transit Use in Toronto, Ontario, Canada. Issue 1 (January 2014) - Foth, Nicole; Manaugh, Kevin; El-Geneidy, Ahmed M.
Increasing public transit ridership is a goal for most transit agencies and plays a central role in many recent regional transportation plans. Therefore, a comprehensive understanding of the determinants of mode choice and their effects over time is important. This study sought to understand how accessibility to employment by public transit changes over time, and how this accessibility explains changes in transit use. With the use of linear regression analysis, the authors explored the influence of job accessibility, transport infrastructure, and social disadvantage on transit mode share for three job categories in Toronto, Ontario, Canada, in 2 years, 1996 and 2006. New transit infrastructure did not necessarily attract more transit commuters but was found to affect commuting to different job categories differently. Also, new highway infrastructure hampered transit mode share, regardless of job type. The aggregate all-jobs model was found to dilute some differences between the transit mode choices of people commuting to different job categories. Finally, increases in accessibility by transit were found to augment transit mode share, while people in more socially disadvantaged areas were more likely to commute by transit in any job category. This study reveals findings that may be of interest to land use and transportation planners working toward boosting regional transit ridership, while also attaining social equity goals.